(3eHOC GdMQjI GdfbGHjI defXeGJ GdYeGd (B: s (3OQGSI ebGQfI (B/ s - (3eMeO CMeO ESeGYjd s; (3GgGH ESeGYjd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1982)
(3JgOa gPg GdOQGSI Gdi GdJYQa Ydi eGgjI eHOC GdMQjg GdfbGHjg HYfGUQg hebGjjSg GdeMOOg ai GdfXGe GdOhdi hJbhe Ydi efgL ebGQfg GdbhGYO GdeJYdbg HGdeHOC ai GdfXGe GdbGfhfi GdhWfi HHYV GdfXe GdGLfHjg (B( (3GdeHOC ai GdfXe GddjHQGdjg hgh GdfXGe GdaQfSi hGdKGfi jLSO GdNUGFU GdeJejRg ddeHOC ai GdfXe GdGTJQGcjg hgh GdfXGe GdShajJi eY GdGTGQI dHYV GdJTQjYGJ GdYQHjg(B) (3hQO gPg GdebGQfg ai cd GdMGdGJ Gdi GdebGjjS GdOhdjg GdJi CcOJ QLGMJgG hJYJeO gPg GdOQGSg Ydi GHQGR GhLg GdbUhQ ai GdVeGfGJ GdJTQjYjg GdebQQg dcaGdg JWHjb GdeHOC hJhVjM MGdGJ GdeSGS Hg Ydi UYjO GdhGbY hGdJhUjGJ GdJi bOeJgG ai gPG GdTCf GddLGf GdOhdjg Gdecdag HeQGbHI JWHjb GJaGbjGJ GdMQjg GdfbGHjg hJHOC GdOQGSI HHGH JegjOi ddJYQa Ydi GdefXeg GdfbGHjg dJMOjO eGgjJgG GdbGfhfjg hGdbGA GdVhA Ydi JGQjN GdfVGd GdYeGdi ef CLd GfJUGQ eHOC GdMQjg GdfbGHjg ceG jYQV gPG GdHGH GLeGdG ddfXe GdfbGHjg GdeYGUQg hjbOe GdHGH GdGhd OQGSI dYfGUQ eHOC GdMQjg GdfbGHjg ef RhGjG MQjI GdJchjf GdfbGHi HOhf JQNjU eSHb HOhf JejjR Hjf GdYeGd , MSH GNJjGQge , MQjI GdfbGHI ai GNJjGQ bGOJgG hJSjjQ GehQgG hGdVeGfGJ GdJi Jcad MQjI GfbVGFgG GeG GdHGH GdKGfi ajOQS MQjI eeGQSI GdhXjag GdfbGHjg heTcdI JMOjO fWGb gPg GdhXjaI hebJVjGJ eeGQSJgG hYdGbg GdfbGHg HGdOhdg hGdGMRGH eY JbOje feGPL Yedjg JLSO GdeTGcd GdeJUdg HMQjI eeGQSI GdfbGHGJ dGfTWJgG hCSJbdGdgG Yf GdOhd hGdGMRGH CeG GdHGH GdKGdK abO NUU GdOQGSI GdeVehf GdaQOi ddMQjg GdfbGHjg HeXgQg GdGjLGHi heXgQg GdSdHi hGNjQG MQjI GdGfSMGH ef GdfbGHg Ke JCJi GdNGJeg dJbOe HYV ebJQMGJ GdHGMK GdJi jecf Gf Jchf eMd OQSI ef Gdabg hGdeTQY HbUO JYRjR ecGfI eHOC GdMQjg GdfbGHjg ai fXGefG GdbGfhfi HeG jJab eY Ggejg GdeJYGXeg(B.s
(3jTJed Ydi edGMb UaMGJ(B: 411 - 420s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1982.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ(B: 421 - 435s
Keywords: (3GdJTQjYGJ GdGLJeGYjIs; (3GdefXeI GdfbGHjIs; (3JGQjN GdfbGHjI GdeUQjIs; (3MQjI JCSjS GdfbGHIs; (3eHOC GdJYOO GdfbGHjs; (3MQjI GNJjGQ GdbjGOGJ GdfbGHjIs; (3GdhXjaI GdfbGHjIs; (3MQjI GdGfVeGe GdfbGHjs; (3CReI GdMQjI GdfbGHjI HJhfSs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs